A Case Study on Experiential Learning in Architecture: Accessible, Climate-Responsive, and Flexible House Designs - Avci, Ali Berkay; Beyhan, Şefika Gülin (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
: Architectural education is based on acquiring theoretical and applied knowledge. As a result, experiential learning theory was frequently applied to architecture design courses. As experiential learning refers to gaining knowledge by doing, it allows the students to experience implementing the theoretical knowledge and refine their design solutions by communicating with the teachers. The present study aims to integrate experimental learning in a theoretical course named